Chlamydia psittaci and ocular adnexal lymphomas (Hematology Meeting Reports, 2009)
Infectious agents, including bacteria, have been variously associated with lymphomagenesis and, in some cases, regarded as targets for new therapeutic approaches. Several lines of evidence indicates that ocular adnexal lymphomas (OAL) may be antigen-driven disorders, although the source of the putative antigen(s) is still unknown. Chlamydiae infection is responsible for inflammatory ocular diseases including chronic follicular conjunctivitis, which could provide persistent antigenic stimulation. On these grounds, we have carried out a study aimed to assess whether infection by Chlamydiae is associated with the development of OAL.